Recognizing culture based religious icons from Muslim culture user interface design (MCUID) prototype - Nasruddin, Zan Azma; Hussin, Husnayati (Design for Scientific Renaissance, 2015)
The phenomena nowadays, numbers of metaphor worlds and their participants that growing rapidly, primarily is a Western Culture dominated environment. Attention paid to other cultures is still very little. There is an assumption that if metaphor worlds are to become a truly global platform for users then it will be essential to "encode" the flexibility for social interactions to take place in a way that is sensitive to other cultures and most important matters that could give values to the target users. It is understood by muslims that Allah has used metaphor to send His messages to mankind through Al Quran. Inspired from it, the key concern is to shift the focus of development from standard interface design to Islamic interface design. A framework has been developed adapted from Culture Centered Design. Important factors have been added to the framework especially on Islamic values as a way of life and a journey towards Allah. Further more, an interface prototype known as Muslim Centered User Interface Design (MCUID) prototype is created. This paper focused on the empirical investigation through interface recognition test using closed card sorting technique towards the prototype. The analysis tabulated the patterns of Muslim users’ perceptions using Atlas.ti 7 both in qualitative and quantitative measurements.